Concurrent and rapid recovery of bacteria and protist communities in Canadian boreal forest ecosystems following wildfire. (December 2021) - Dai, Zhongmin; Lv, Xiaofei; Ma, Bin; Chen, Na; Chang, Scott X.; Lin, Jiahui; Wang, Xuehua; Su, Weiqin; Liu, Huaiting; Huang, Yanlan; Hu, Caixia; Luo, Yu; et al.
Abstract: Wildfire plays an important role in restructuring bacterial and protist taxonomic and functional communities in forest ecosystems. Yet, the recovery of bacterial and protist communities following wildfire has not been rigorously investigated across long-term wildfire chronosequences. We compared changes in bacterial and protist alpha diversity, community composition, co-occurrence networks and determinant edaphic factors between burnt and unburnt (reference) soils at 11 different sites representing a 76-year wildfire chronosequence in Canadian boreal forests. The fire increased bacterial and protist alpha diversity and altered community composition (beta diversity) as compared to the site-specific controls during the early recovery stage (<5 years since fire), but had no effect on bacterial and protist communities in the middle (8–20 years) and late (>30 years) recovery stages. Bacterial and protist communities showed similar patterns of change across the wildfire chronosequence. The post-fire recovery of bacterial communities was associated with changes in soil chemical properties ( e.g., nutrient status and pH) and vegetation succession. The protist community assembly was co-influenced by changes in bacterial communities and vegetation succession/soil properties. The concurrent recovery of bacterial and protist communities, and their influencing factors of vegetation and soil properties, imply the above- and belowground living communities are strongly linked in wildfire-perturbed forest ecosystems. Graphical abstract: Image 1 Highlights: Fire increased bacterial and protist alpha diversity during the early recovery stage. Fire did not affect bacterial and protist communities in middle/late recovery stages. Recovery of protist communities was associated with changes in bacterial communities. Protist community assembly was co-determined by changing biotic and abiotic factors.